The Gini coefficient as a measure of disproportionality - Dniestrzański, Piotr (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
Measures of inequality, properly adapted, often tend to be used as a tool to address the issue of disproportionality. The most popular of them, such as the Gini or Atkinson coefficient, or entropy coefficient can, under certain circumstances, act as measures of disproportionality. However, one must specify precisely what is to be measured and interpret the results consistently. In this paper we analyze what confusion or outright errors can be committed when using inequality coefficients. The presented analysis is aimed at the Gini coefficient, however, the problem also applies to the rest of the coefficients.
Didactics of Mathematics, 2015, Nr 12 (16), s. 25-34
Keywords: inequality measure; the Gini coefficient; mathematics teaching